ANALISIS KESULITAN BELAJAR MATEMATIKA SISWA KELAS III SDN 3 TERONG TAWAH TAHUN AJARAN 2020/2021 - Rosidah Rosidah; Lalu Hamdian Affandi; Awal Nur Kholifatur Rosyidah (Program Studi PGSD, FKIP, Universitas Mataram, 2022)
Mathematics is a universal science that underlies the development of modern technology. In the reality, mathematics learning activities have a higher level of learning difficulty compared to other subjects, especially in fractional operations. This can be seen when the learning process takes place, the lack of interest and attention of students towards learning mathematics, students passive interaction with the teacher and the use of conventional methods as learning methods. This study aims to determine the types of learning difficulties in mathematics on the material of fractional arithmetic operations and the improvement efforts made by teacher in class III SDN 3 Terong Tawah in overcoming students' learning difficulties. This research is a qualitative research that apply descriptive method. The research was conducted at SDN 3 Terong Tawah with the research subjects with the research subjects being 6 third grade students who had difficulty learning mathematics and who scored below the KKM. Data collection techniques using diagnostic tests, interviews and documentation. Data analysis of Interactive Analysis Method. The results of the study showed that students had difficulty learning the material for fractional arithmetic operations. The types of mathematical difficulties experienced by students are difficulties in reading and understanding the meaning of the questions, difficulties in understanding mathematical concepts in fractional counting operations material, and students having difficulty in processing skills in working on fractional arithmetic operations. The improvement efforts used by the third grade teacher of SDN 3 Terong Tawah are by holding special tutoring, repeating material that has not been understood by students and making improvements or remedial to students who get scores below the KKM.